(NsO^INENIQ (B/s (N~ASTX (B1s - (NlERMONTOW(B, (NmIHAIL `RXEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1988)
(Nw PERWYJ TOM (B"(NsO^INENIJ(B" (NWYDA@]EGOSQ RUSSKOGO PO\TA m(B. (N`(B. (NlERMONTOWA WO[LI STIHOTWORENIQ (B1828 - 1841 (NGG(B. (NI PO\MY (B("(NkAWKAZSKIJ PLENNIK(B", "(NkORSAR(B", "(NdEMON(B", "(NmCYRI(B" (NI DR(B.)s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs